2009
DOI: 10.1902/jop.2009.090044
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Penetration Through Antibiotic‐Loaded Guided Tissue Regeneration Membranes

Abstract: The results showed that penetration of S. mutans and A. actinomycetemcomitans through amoxicillin- or tetracycline-loaded ePTFE membrane, glycolide fiber membrane, and collagen membrane was delayed and/or reduced. Thus, incorporation of an antibiotic into the membrane may be of value when controlling membrane-associated infection during GTR therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…However, most of the membrane materials used for GTR/GBR, such as collagen, has no inhibitory effect on bacterial growth. Previous studies showed that GTR membranes loaded with antibiotic drugs could delay and/or reduce bacterial penetration30 and enhance the formation of the attachment of PDL cells in the presence of oral pathogens 31. Therefore, using materials that possess antibacterial property as GTR membranes should achieve the same effect as the above and will present more superiority.…”
Section: Periodontal Regenerationmentioning
confidence: 99%
“…However, most of the membrane materials used for GTR/GBR, such as collagen, has no inhibitory effect on bacterial growth. Previous studies showed that GTR membranes loaded with antibiotic drugs could delay and/or reduce bacterial penetration30 and enhance the formation of the attachment of PDL cells in the presence of oral pathogens 31. Therefore, using materials that possess antibacterial property as GTR membranes should achieve the same effect as the above and will present more superiority.…”
Section: Periodontal Regenerationmentioning
confidence: 99%
“…In addition, most of the membranes-also called barriers-protect the defects from the periosteum, which is necessary for angiogenesis. Due to this, wound healing disturbances often occur 11 and reduce the positive effect of augmentation.…”
Section: Guided Tissue Regenerationmentioning
confidence: 99%
“…Wound healing disturbances occur in a high amount of surgical treatments in this position. 2,11 Some authors report on adding platelet-rich plasma (PRP) to the augmentation material to enhance the bone development and healing of the soft tissue. [12][13][14] The use of PRP therapy in surgery was introduced in the late 1990s.…”
Section: Introduction and Scientific Backgroundmentioning
confidence: 99%
“…One study assessed explicitly the penetration of prokaryotic cells, namely of S. mutans and A. actinomycetemcomitans through guided tissue regeneration (GTR) membranes using a device consisting of an inner tube and an outer bottle filled with culture media. The study showed differences in the behavior of the evaluated membranes and -not surprisingly -that an incorporation of an antibiotic into the membrane was effective in controlling bacterial percolation [6]. According to the authors' knowledge studies using such models are, however, still lacking the evaluation of eukaryotic cells.…”
Section: Introductionmentioning
confidence: 96%